Characterization of acid: Induced gels of quinoa proteins and carrageenan - Montellano Duran, Natalia (2019)
In this work acid-induced gels composed of both quinoa proteins (QP, 18–42 g/L) and ι–carrageenan (Carr, 0–0.5 g/L) were characterized. The objective of this work was to characterize gels with different structures and to correlate their microstructural parameters to physical properties of gels using modeling equation. Aggregates and pores size distributions were determined using confocal laser scanning microscopy; the medians of these distributions being between 1.10–2.46 μm and 1.4–4.45 μm respectively. Digital homogeneity of the images was also estimated by the determination of the angular second moment (13–54). Water holding capacity (WHC), color, appearance and texture were measured in order to assess the macrostructure. Appearance and color (L* = 82–87, a* = 3.52–6.09, b* = 15.8–24.4) were affected by QP concentration and the glucono–δ–lactone (GDL, 0–21 g/L) to QP mass ratio (GDL/QP), probably due to the protein coloration and the final pH reached by the system. WHC (82–97%) and textural (stiffness = 12–253.2 N/mm, maximum force = 127.4–1298.5 N) properties were affected by the concentration of both biopolymers, GDL/QP and their combination. The pore size showed to be correlated to mechanical properties of the gels as well as to their WHC and appearance. Gels obtained were a result of the competition of QP–QP interaction with QP–Carr interaction.